Do pre-natal and post-natal economic shocks have a long-lasting effect on the height of 5-year-old children? Evidence from 20 sentinel sites of rural and urban Ethiopia - Woldehanna, T (Young Lives, 2010)
While the Ethiopian national emergency and food security programmes support farmers hit by area-wide shocks such as crop failure brought about by drought, insects and pests, idiosyncratic shocks such as illness and death of household member, loss of assets and separation of family or divorce are not covered by any of the current programmes. In the absence of social assistance programmes to support vulnerable households, these idiosyncratic shocks may lead to serious malnutrition among poor children. Using longitudinal data of children collected at the age of 1 and 5 years (Young Lives younger cohort data), we examined the existence of permanent consequences of early childhood malnutrition and recovery of children from their early childhood malnutrition plus the persistent effect of pre-natal and post-natal economic shocks on child health and nutritional achievement, as measured by z-score of height-for-age and log of height of 5-year-old children. We employed OLS, instrumental variable (IV) and generalised method of moment estimation methods controlling for community fixed effects. Our results confirmed the existence of permanent consequences of early childhood malnutrition and also the potential for the strong recovery of children from their initial early malnutrition. We also found significant effects on zscore of height-for-age and log of height, not only for post-natal economic shock but also the pre-natal economic shocks, implying the long-term consequence of shocks on children’s height.In addition to area-wide shocks including crop failure brought about by drought, insects and pests, we found that idiosyncratic shocks such as separation of family, death of breadwinners and unavailability of food are also important determinants of malnutrition. Although area-wide economic shocks are very important and it would be good for the government to focus more on them, idiosyncratic shocks also have a considerable contribution to make to the improvement of children’s z-score of height-for-age and consequently to the reduction of stunting and severe stunting in Ethiopia. Therefore, it is still worthwhile to ensure that government assistance programmes cover idiosyncratic shocks such as death and illness of household members and separation of family or divorce. Also, since rural children are more vulnerable to economic shocks than urban children, it would be beneficial for social assistance programmes to focus more on rural areas.